The Use of Eleven Translation Techniques in Translating a Webtoon Comic by Dito Satrio Suryonugroho Entitled ‘Jajan Squad’ - Rizka Putri Edianza; Artika Wina Fitriani (Jurnal Vokasia, 2023)
This article is the activities collected Indonesian transcript data from the web comic "Jajan Squad" which is translated into English as primary data obtained by reading from Webtoon Application. The "Jajan Squad" webcomic is a slice of life genre published on the Webtoon application in 2017. 'Jajan Squad' is among the top 25 most favourite webtoon comic based on the most loves and readers. The purposes of translating 'Jajan Squad' Webcomic is to translate the web comic from Indonesian into English, explain the process and techniques in translation, explain the obstacles during translation, and explain the solutions to overcome obstacles in translation. There are 11 translation technique (out of 18) used from Molina and Albir. The literal technique is most frequently used in webcomic translation, because there are many sentences that are translated word by word. The conclusion is that this job training report was conducted according to the translation process and only used 11 translation techniques (out of 18).